Acetazolamide Treatment Prevents Redistribution of Astrocyte Aquaporin 4 after Murine Traumatic Brain Injury. (2nd May 2019) - Glober, Nancy K.; Sprague, Shane; Ahmad, Sadiya; Mayfield, Katherine G.; Fletcher, Lauren M.; Digicaylioglu, Murat H.; Sayre, Naomi L.
Abstract : After traumatic brain injury (TBI), multiple ongoing processes contribute to worsening and spreading of the primary injury to create a secondary injury. One major process involves disrupted fluid regulation to create vascular and cytotoxic edema in the affected area. Although understanding of factors that influence edema is incomplete, the astrocyte water channel Aquaporin 4 (AQP4) has been identified as an important mediator and therefore attractive drug target for edema prevention. The FDA-approved drug acetazolamide has been administered safely to patients for years in the United States. To test whether acetazolamide altered AQP4 function after TBI, we utilized in vitro and in vivo models of TBI. Our results suggest that AQP4 localization is altered after TBI, similar to previously published reports. Treatment with acetazolamide prevented AQP4 reorganization, both in human astrocyte in vitro and in mice in vivo. Moreover, acetazolamide eliminated cytotoxic edema in our in vivo mouse TBI model. Our results suggest a possible clinical role for acetazolamide in the treatment of TBI.